Odpowiedź :
Odpowiedź:
Wszystkie spełniają
Szczegółowe wyjaśnienie:
5- 0²+1=5+1=6
6-0²=6
L=P
5-5²+1=5-25+1=-20+1=-19
6-5²=-19
L=P
5-(-5)²+1=5-25+1= -19
6-(-5)²=-19
L=P
5-(-6)²+1=5-36+1=-31+1=-30
6-(-6)²=6-36=-30
L=P
5-6²+1=-30
6-6²=-30
[tex]5 - {x}^{2} + 1 = 6 - {x}^{2} \\ 5 + 1 = 6 \\L = P [/tex]
Sprawdzenie każdej liczby
[tex]5 - {6}^{2} + 1 = 6 - {6}^{2} \\ 5 - 36 + 1 = 6 - 36 \\ - 30 = - 30 \\ L = P[/tex]
[tex]5 - {5}^{2} + 1 = 6 - {5}^{2} \\ 5 - 25 + 1 = 6 - 25 \\ - 19 = - 19 \\ L = P[/tex]
[tex]5 - ( - 6 {)}^{2} + 1 = 6 - ( - {6)}^{2} \\ 5 + 36 + 1 = 6 + 36 \\ 42 = 42 \\ L = P[/tex]
[tex]5 - ( - 5 {)}^{2} + 1 = 6 - ( - 5 {)}^{2} \\ 5 + 25 + 1 = 6 + 25 \\ 31 = 31 \\ L = P[/tex]
[tex]5 - ( {0)}^{2} + 1 = 6 - ( {0)}^{2} \\ 5 - 0 + 1 = 6 - 0 \\ 6 = 6 \\ L = P[/tex]
Odp. Każda liczba spełnia równanie